Coronary vasospasm testing: escape from the cath lab! - Ana Djordjevic Dikic; Srdjan Dedic; Nikola Boskovic; Vojislav Giga (Exploration of Cardiology, 2024)
Coronary vasospasm stands as a widely acknowledged and frequent culprit behind chest pain, acute coronary syndrome, and sudden cardiac death, yet it remains a challenging diagnosis. Current guidelines recommend invasive coronary function testing to assess pathophysiology and mechanisms and to define treatment. In reality, this protocol is rarely applied, because it necessitates extended occupation of the cath lab, repetitive administration of nephrotoxic iodine contrast agents, the need for repeated testing on both coronary arteries leading to considerable radiation exposure, and significant direct expenses. The promising perspective for vasospasm testing is a noninvasive approach with advanced echocardiographic techniques, such as transthoracic Doppler echocardiography, with more sensitive indicators of ischemia. Hyperventilation and exercise tests are used for vasospasm directed testing, with assessment of the new parameters: coronary flow velocities and reserve, allowing to see deeper into macro and microvascular pathophysiology. Association between coronary flow, global longitudinal strain and microvascular dysfunction (MVD) and impaired values at hyperemia was previously demonstrated. Reduction in coronary flow velocity (CFV) despite heightened myocardial oxygen consumption and double product during hyperventilation are indicative of coronary vasospasm. Normal coronary angiography finding in patients with documented evidence of ischemia should initiate additional diagnostic testing in order to increase the yield of specific diagnosis in patients with suspected vasospasm, which could help to personalize treatment and prognosis. In order to achieve this, non-invasive provocative stress echocardiography tests should be included in the diagnostic workup. This approach, characterized by its simplicity, feasibility, safety, and efficacy, is currently undergoing extensive testing on a large scale.